Laser-Induced Point Defects in Fused Silica Irradiated by UV Laser in Vacuum - Xiaoyan Zhou; Xinda Zhou; Jin Huang; Qiang Cheng; Fengrui Wang; Xin Ye; Xiaodong Jiang; Weidong Wu (Advances in Condensed Matter Physics)
High-purity fused silica irradiated by third harmonic of the Nd:YAG laser in vacuum with different laser pulse parameters was studied experimentally. Laser-induced defects are investigated by UV spectroscopy, and fluorescence spectra and correlated to the structural modifications in the glass matrix through Raman spectroscopy. Results show that, for laser fluence below laser-induced damage threshold (LIDT), the absorbance and intensity of fluorescence bands increase with laser energies and/or number of laser pulses, which indicates that laser-induced defects are enhanced by laser energies and/or number of laser pulses in vacuum. The optical properties of these point defects were discussed in detail.